Assessing the Efficacy of Broad-Spectrum Antibiotics in Controlling Bacterial Contamination in the In Vitro Micropropagation of Ginger (Zingiber officinale Rosc) - Selam Tewelde; Subban Patharajan; Zenebe Teka; Desta Berhe Sbhatu (The Scientific World Journal)
Ginger (Zingiber officinale Rosc) (Zingiberaceae) is a livelihood and commercial crop in Ethiopia. But, the availability of clean and healthy planting materials has become a problem due to wilt disease, caused by Ralstonia solanacearum Biovar 3 Race 4. This problem obliged growers to seek for tens of millions of vigorous and disease-free planting materials very quickly via in vitro micropropagation of shoot tip explants. For this purpose, protocols of sterilizing shoot tip explants and controlling bacterial contamination of one Ethiopian ginger cultivar called Deribo were tested. Hence, this article reports the finding of a study that aimed at testing the (a) effectiveness of three sterilization agents, namely, 0.25% w/v RBK (composed of ridomile, bayleton, and kocide at 1 : 1 : 1 ratio), 0.50% v/v NaOCl, and 70% v/v ethanol at three different treatment times in combination with 0.25% HgCl2; (b) efficacy of four broad-spectrum antibiotics and their combinations in controlling bacterial contaminants of ginger shoot tip explants and in vitro micropropagation media; and (c) effects of the antibiotics on the shooting performances of the explants of the cultivar. A 0.50% v/v NaOCl at exposure time of 20 min followed by 0.25% HgCl2 has resulted in 80% contamination-free and 70% live explants after three weeks of incubation. Likewise, cefotaxime at 50, 100, and 200 mg/L and cefotaxime plus streptomycin at 25, 50, and 100 mg/L yielded 87 to 93% contamination-free microshoots after three weeks of culturing. The number of explants killed by the antibiotics increased with increasing the concentration of the antibiotics. Cefotaxime at 50 mg/L and cefotaxime plus streptomycin at 25 mg/L yielded significantly highest mean microshoots per explant (7.10 ± 0.36 and 7.51 ± 0.27, respectively) and mean shoot length (4.2 ± 0.26 and 3.56 ± 0.17 cm, respectively). Some of the microshoots showed some yellowing. But, they turned green and grew normal after subcultured into fresh, antibiotics-free culture media. These findings are important foundations towards developing more optimized protocols of sterilizing explants and controlling bacterial contaminants for large-scale in vitro micropropagation of the Deribo ginger cultivar.